Teratogenic Effect of Congenital Toxoplasmosis in Chicken Embryo - Suwanti, Lucia Tri; Mufasirin, Mufasirin; Plumeriastuti, Hani; Safitri, Erma (KnE Life Sciences, 2017)
This research is designed to observe the teratogenic effect of Toxoplasma gondii infection in chick embryos, based on the number of somites, embryo length and the development of embryonic brain vesicles. Methods in the research: Chicken eggs were infected with 1 x 103 tachyzoites of T. gondii. The eggs were incubated in eggs hatching box. Observation of somite performed on embryonated eggs 24 hours after incubation and the embryonic development of vesicles performed 72 hours after incubation then the length of each embryo were measured. Results: Revealed that there was a significant difference in the number of somites (p < 0.1), T. gondii infection reduced the number of somites. While in the number of brain vesicles in 3 - days old chicken embryos, although there was no significant difference, the size declining emerged. The length of the embryos both at 24 or 72 hours old showed that T. gondii infection reduced the length (p < 0.1). Conclusions: T. gondii infection influences the development of chicken embryos in the declining of length and the decreasing of somite embryo number. Keywords: IGF-I crossbreed mare serum pregnant; Follicle; Mus musculus